National seroepidemiological study of COVID‐19 after the initial rollout of vaccines: Before and at the peak of the Omicron‐dominant period in Japan. Issue 2 (1st February 2023) - Arashiro, Takeshi; Arai, Satoru; Kinoshita, Ryo; Otani, Kanako; Miyamoto, Sho; Yoneoka, Daisuke; Kamigaki, Taro; Takahashi, Hiromizu; Hibino, Hiromi; Okuyama, Mai; Hayashi, Ai; Kikuchi, Fuka; et al.
Abstract: Background: Based on routine surveillance data, Japan has been affected much less by COVID‐19 compared with other countries. To validate this, we aimed to estimate SARS‐CoV‐2 seroprevalence and examine sociodemographic factors associated with cumulative infection in Japan. Methods: A population‐based serial cross‐sectional seroepidemiological investigation was conducted in five prefectures in December 2021 (pre‐Omicron) and February–March 2022 (Omicron [BA.1/BA.2]‐peak). Anti‐nucleocapsid and anti‐spike antibodies were measured to detect infection‐induced and vaccine/infection‐induced antibodies, respectively. Logistic regression was used to identify associations between various factors and past infection. Results: Among 16 296 participants (median age: 53 [43–64] years), overall prevalence of infection‐induced antibodies was 2.2% (95% CI: 1.9–2.5%) in December 2021 and 3.5% (95% CI: 3.1–3.9%) in February–March 2022. Factors associated with past infection included those residing in urban prefectures (Tokyo: aOR 3.37 [95% CI: 2.31–4.91], Osaka: aOR 3.23 [95% CI: 2.17–4.80]), older age groups (60s: aOR 0.47 [95% CI 0.29–0.74], 70s: aOR 0.41 [95% CI 0.24–0.70]), being vaccinated (twice: aOR 0.41 [95% CI: 0.28–0.61], three times: aOR 0.21 [95% CI: 0.12–0.36]), individuals engaged in occupations such as long‐term care workers (aOR: 3.13 [95% CI: 1.47–6.66]), childcare workers (aOR: 3.63 [95% CI: 1.60–8.24]), food service workers (aOR: 3.09 [95% CI: 1.50–6.35]), and history of household contact (aOR: 26.4 [95% CI: 20.0–34.8]) or non‐household contact (aOR: 5.21 [95% CI:3.80–7.14]) in February–March 2022. Almost all vaccinated individuals (15 670/15 681) acquired binding antibodies with higher titers among booster dose recipients. Conclusions: Before Omicron, the cumulative burden was >10 times lower in Japan (2.2%) compared with the US (33%), the UK (25%), or global estimates (45%), but most developed antibodies owing to vaccination.